Comparative analyses of chloroplast genomes in Geum species: insights into genome characteristics, phylogenomic implications, and adaptive evolution - Fu, Wen-Tao; Zhang, Zhi-Ping; Guo, Jia-Jie; Wen, Jun; Li, Qin-Qin (Frontiers in Plant Science, 2025)
The genus Geum, comprises about 72 species, most frequently distributed in North America, Asia, and Europe, with a few representatives in South America, South Africa, Australia, and New Zealand. Previous phylogenetic analyses based on several molecular markers have contributed to understanding the delimitation of Geum, but the phylogenetic relationships within the genus remain unresolved. Moreover, only a few chloroplast (cp) genomes of Geum species have been reported, and no comparative cp genome analyses among Geum species have been conducted to date, limiting our understanding of cp genome evolution. This study is the first to conduct comparative genomic analyses on the cp genomes of 32 accessions representing 11 Geum taxa. The Geum cp genomes showed a typical quadripartite structure, similar to that of most other land plants, with a total of 129 genes, including 84 protein-coding genes (PCGs), 37 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The Geum cp genomes were conserved in structure, size, GC content, gene order, and gene content. Eleven highly variable regions (3′-trnK-UUU-matK, psbZ-trnG-GCC, trnR-UCU-atpA, petA-psbJ, 5′-trnK-UUU-rps16, rps16-trnQ-UUG, rpl32-trnL-UAG, ndhF-rpl32, trnS-GCU-trnG-UCC, ndhC-trnV-UAC, and petN-psbM) were identified as candidate molecular markers for future studies on population genetics and systematic evolution of Geum species. Phylogenetic analyses provided new insights into the relationships among Geum species and supported Smedmark’s recircumscription of Geum in a broad sense, corroborating the inclusion of Acomastylis, Coluria, and Taihangia within Geum. Twenty-three genes with sites under positive selection were detected, and the adaptive evolution of these genes may play important roles in the adaptation of Geum species to their habitats. Overall, this study enhances our understanding of the cp genome characteristics, phylogeny, and adaptive evolution of Geum species.